1992
DOI: 10.1086/209294
|View full text |Cite
|
Sign up to set email alerts
|

The Consciousness of Addiction: Toward a General Theory of Compulsive Consumption

Abstract: This article reviews and integrates recent theories of addiction drawn from a diverse set of disciplines-consumer behavior, medicine, sociology, psychiatry, and psychology-to provide a comprehensive framework for understanding the etiology of addiction and other compulsive consumer behaviors. Interpretive material from personal interviews with addicted and nonaddicted drug users is then used to illustrate the consciousness of addictive consumption. Two a priori themes-serial/simultaneous addictions and persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
276
0
69

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 452 publications
(346 citation statements)
references
References 25 publications
1
276
0
69
Order By: Relevance
“…On the other hand, evidence shows that a considerable number of consumers think of themselves as "impulse buyers. " Between 1975 and1992, an average of 38 percent of the adults in an annual national survey responded affirmatively to the statement: "I am an impulse buyer" (DDB Needham Annual Lifestyle Survey 1974. There are also several studies that have indicated the significant and growing trend toward unplanned purchasing.…”
Section: The Nature Of Impulse Buyingmentioning
confidence: 99%
“…On the other hand, evidence shows that a considerable number of consumers think of themselves as "impulse buyers. " Between 1975 and1992, an average of 38 percent of the adults in an annual national survey responded affirmatively to the statement: "I am an impulse buyer" (DDB Needham Annual Lifestyle Survey 1974. There are also several studies that have indicated the significant and growing trend toward unplanned purchasing.…”
Section: The Nature Of Impulse Buyingmentioning
confidence: 99%
“…This has happened because the majority of players are doing broadly the same things more intensively. Forming a relationship with the consumer creates an exponentially profi table business model that is sustainable in the long term, across many business domains and customer types ( Hirschman, 1992 ). Holbrook (2000) believes that when we enter the era of experiential marketing, the focus will shift from product performance and benefi t to experiences entertainment.…”
Section: Introductionmentioning
confidence: 99%
“…As pesquisas do comportamento do consumidor de Hassay e Smith (1996) sugerem que uma série de formas de consumo são motivadas pelo impulso compulsivo. Esses pesquisadores relatam que os comportamentos de consumo, tais como a compra por impulso (Rook & Hoch, 1985;Rook, 1987), compra compulsiva (Faber & O'guinn, 1988;(Burns, Gillett, Rubinstein, & Gentry, 1990Faber & O'Guinn, 1992), a cleptomania (McElroy, Keck, Pope, & Hudson, 1989) e consumo compulsivo (Hirschman, 1992) são diversamente motivados por fatores como sentimentos de ansiedade, tensão, desejos, anseios que geram necessidade de preenchimento emocional por meio da compra.…”
Section: Referencial Teóricounclassified
“…As consequências do consumo compulsivo muitas vezes levam a um aumento das dívidas de cartão de crédito (Ruvio, Somer, & Rindfleisch, 2014), maior conflito conjugal, e diminuição da auto-estima, que é susceptível de produzir maior estresse e menor bem-estar (Hirschman, 1992).…”
Section: Referencial Teóricounclassified
See 1 more Smart Citation